Pemahaman Mendalam: Jihad Intelektual dalam Pendidikan Agama Islam - Sali, Muhammad (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2023)
This research aims to examine the concept and relationship between jihad and science in the context of Islam, this research discusses the history of jihad, the definition of jihad, the importance of jihad, the definition of Islamic science. In addition, this research also identifies the types and levels of jihad, the kinds of jihad, and the purpose and objectives of jihad in Islam. This research method provides an extensive literature study of primary and secondary sources related to jihad, Islamic science, and the thoughts of Islamic scholars. Classical texts such as the Qur'an, Hadith, were used as the main references. The results of this study reveal that jihad in Islam has a long history that involves spiritual, moral, and physical dimensions. The definition of jihad includes individual efforts to improve themselves, fight lust, and protect religion and Muslims from threats. Islamic religious knowledge is important in understanding and implementing jihad correctly, because it requires a deep understanding of religious principles and teachings. The connection between jihad and Islamic religious knowledge lies in the importance of deep religious knowledge to carry out jihad properly and avoid wrong or extreme understanding. Jihad is divided into several types and levels, including jihad with conscience. Each type of jihad has its own role in protecting and strengthening Islam and building goodness in the world. Jihad with Islamic knowledge is a call for Muslims to continue to learn, understand, and implement religious teachings correctly. Religious knowledge is an important foundation in implementing jihad in a balanced, responsible manner, and based on a deep understanding of Islamic teachings.